2017
DOI: 10.18533/ijbsr.v6i12.1017
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Oil Price Volatility on the Economic Sectors of Libya

Abstract: Fluctuations in oil price and its impact on economic development is an important issue facing a growing number of world economies. A simple changes in oil prices lead to negative or positive effects on all the economic sectors. This paper seeks to investigate the impact of oil price volatility on economic sectors in the Libyan economy context on the basis of annual data spanning from 1968-2012. The Johansen based Co-integration technique is applied to examine the sensitivity of economic sectors to volatility i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
7
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 15 publications
1
7
0
Order By: Relevance
“…A wide range of empirical and theoretical studies have been done on the influence of the oil price change on the economic growth both in the developed and developing countries including Nigeria [1,11,14,27,[29][30][31]33,34,[36][37][38][41][42][43][44][45][46][47][48][49][50]. However, the results of these studies are mixed and conflicting.…”
Section: Literature Reviewmentioning
confidence: 99%
See 4 more Smart Citations
“…A wide range of empirical and theoretical studies have been done on the influence of the oil price change on the economic growth both in the developed and developing countries including Nigeria [1,11,14,27,[29][30][31]33,34,[36][37][38][41][42][43][44][45][46][47][48][49][50]. However, the results of these studies are mixed and conflicting.…”
Section: Literature Reviewmentioning
confidence: 99%
“…While some claim that oil price fluctuation exerts adverse impact on macroeconomic variables [1,[7][8][9][10][11]; others found that crude oil price fluctuation exert positive influence on the economic growth [16,37,48,50]. Still, some others argue that the effects are less disruptive and also not as significant as thought since oil is becoming less relevant in the economic equation of many countries in the recent time [19,36,[51][52][53][54][55], while others found that the effect is asymmetric and there is no clear effect of oil price changes on the economic growth [41,[56][57][58][59] since the impact of oil price fluctuations is considered to be different for oil importing and exporting countries [48].…”
Section: Literature Reviewmentioning
confidence: 99%
See 3 more Smart Citations